Frasa Nomina pada Teks Berita Politik di SuaraMerdeka.com Periode Juli - September 2025 - Natalia Kartika Saputri; Adhisti Kurnia Yulianti; Agnia Faizafika; Bintang Prima Vidyasari; Rangga Saputra; Asep Purwo Yudi Utomo; Uki Hares Yulianti; Arum Yuliya Lestari (Lembaga Pengembangan Kinerja Dosen, 2026)
Language and news have a close relationship because language is a medium to convey news. In news, the use of noun phrases is important to pay attention to, so that there is no misunderstanding. Therefore, this study aims to analyse the use of object phrases in news texts, focusing on their elements, types, and functions. In this research, two approaches are used, namely qualitative descriptive and syntax. The results show that in the news text, there are various variations of noun phrases. This diversity is seen in the different patterns of phrase formation, which differ in structure and constituent elements. The type of noun phrase that is often found is the subordinate noun phrase. The results showed that noun phrases can occupy syntactic functions as long as their use does not exceed the limits of sentence structure. In Indonesian syntax, noun phrases can function as subjects, objects, or descriptions. Therefore, noun phrases play an important role in the formation of a sentence.